NOD2 and TLR2 Signal via TBK1 and PI31 to Direct Cross-Presentation and CD8 T Cell Responses - Corridoni, Daniele; Shiraishi, Seiji; Chapman, Thomas; Steevels, Tessa; Muraro, Daniele; Thézénas, Marie-Laëtitia; Prota, Gennaro; Chen, Ji-Li; Gileadi, Uzi; Ternette, Nicola; Cerundolo, Vincenzo; Simmons, Alison (Frontiers in Immunology, 2019)
NOD2 and TLR2 recognize components of bacterial cell wall peptidoglycan and direct defense against enteric pathogens. CD8+ T cells are important for immunity to such pathogens but how NOD2 and TLR2 induce antigen specific CD8+ T cell responses is unknown. Here, we define how these pattern recognition receptors (PRRs) signal in primary dendritic cells (DCs) to influence MHC class I antigen presentation. We show NOD2 and TLR2 phosphorylate PI31 via TBK1 following activation in DCs. PI31 interacts with TBK1 and Sec16A at endoplasmic reticulum exit sites (ERES), which positively regulates MHC class I peptide loading and immunoproteasome stability. Following NOD2 and TLR2 stimulation, depletion of PI31 or inhibition of TBK1 activity in vivo impairs DC cross-presentation and CD8+ T cell activation. DCs from Crohn’s patients expressing NOD2 polymorphisms show dysregulated cross-presentation and CD8+ T cell responses. Our findings reveal unidentified mechanisms that underlie CD8+ T cell responses to bacteria in health and in Crohn’s.